Prospective Multicenter Study on Early Proximal Tubular Injury in COVID-19–Related Acute Respiratory Distress Syndrome - Mickaël Bobot; Xavier Heim; Howard Max; José Boucraut; Pierre Simeone; Claire Stein; Lionel Velly; Nicolas Bruder; Jean-Marie Forel; Sami Hraiech; Christophe Guervilly; Julien Carvelli; et al. (Kidney International Reports)
Introduction: During COVID-19, renal impairment is associated with poor prognosis in intensive care unit (ICU). We aimed to assess the existence and incidence of early renal dysfunction and its prognostic value in patients with COVID-19–related acute respiratory distress syndrome (ARDS). Methods: In this prospective multicenter study, patients aged over 18 years with invasive mechanical ventilation (MV) for ARDS were enrolled in 3 ICUs. Precise evaluation of renal dysfunction markers, including urinary protein electrophoresis (UPE) and quantification, was performed within 24 hours after MV onset. Results: From March 2020 to December 2021, 135 patients were enrolled as follows: 100 with COVID-19 ARDS and 35 with non–COVID-19 ARDS. UPE found more tubular dysfunction in patients with COVID-19 (68% vs. 21.4%, P < 0.0001) and more normal profiles in patients without COVID-19 (65.0% vs. 11.2%, P = 0.0003). Patients with COVID-19 significantly displayed early urinary leakage of tubular proteins such as beta-2-microglobulin (ß2m) and free light chains, tended to display acute kidney injury (AKI) more frequently (51.0% vs. 34.3%, P = 0.088), had longer MV (20 vs. 9 days, P < 0.0001) and longer ICU stay (26 vs. 15 days, P < 0.0001). In COVID-19 ARDS, leakage of free lambda light chain was associated with the onset of Kidney Disease: Improving Global Outcomes (KDIGO) ≥2 AKI (odds ratio [OR]: 1.014, 95% confidence interval [CI] 1.003–1.025, P = 0.011). Conclusion: Patients with COVID-19–related ARDS display a proximal tubular dysfunction before the onset of AKI, which predicts AKI. Proximal tubular damage seems an important mechanism of COVID-19–induced nephropathy. Analysis of urinary proteins is a reliable noninvasive tool to assess proximal tubular dysfunction in the ICU.